الجراثيم الفوقية المرتبطة بالطحالب البحرية: مصادر محتملة للمواد الصادة للجراثيم - زينب, أسمهان; عباس, آصف (Latakia University Journal -Biological Sciences Series, 2019)
تمّ عزل 230 عزلة جرثومية عن بعض الطحالب البحرية (الخضراء، الحمراء والسمراء) و درست خصائصها الصادة تجاه سلالات جرثومية بيئية ومرضية المنشأ. أظهرت النتائج أن 122 عزلة بنسبة 53.04% تمتلك خاصية التصاد الجرثومي تجاه الجراثيم الإيجابية والسلبية غرام، بنسبة 56.56% و43.44% على التوالي، كما أن الفعالية كانت أعلى تجاه الجراثيم البيئية من الجراثيم الممرضة. لوحظ أيضاً أن معظم الجراثيم الفوقية المدروسة تمتلك خاصية التصاد الجرثومي تجاه المكورات العنقودية الذهبية Staphylococcus aureus الممرضة. كما أبدت الجراثيم المعزولة عن نوعي الطحلب الأخضر Ulva فعالية تجاه جراثيم المكورات الرئوية Streptococcus pneumoniae وجراثيم الكلبسيلا Klebsiella sp. الممرضة، وخاصة الجراثيم المعزولة عن Ulva compressa، أما الجراثيم المعزولة عن الطحالب Ulva compressa و Dictyota spiralis فهي تمتلك فعالية تجاه معظم الجراثيم المدروسة. على ضوء هذه النتائج، يمكن القول إن الجراثيم الفوقية المرتبطة بالطحالب البحرية قد تكون إحدى المصادر الممكنة للمركبات الصادة الطبيعية تجاه الجراثيم. We have isolated 230 strains of epiphytic bacteria from some algae (Chlorophyceae, Rhodophyceae and Phaeophyceae) and investigated for antibacterial activity against environmental and pathogenic bacteria. The results show that (122 isolates) 53.04% of isolates have antibacterial activity against Gram-positive and Gram-negative bacteria, 56.56% and 43.44% respectively, also the antibacterial activity against environmental bacteria was higher than pathogenic bacteria. It was also noted that most of epiphytic bacteria attached on marine algae had antibacterial activity against pathogenic Staphylococcus aureus. Epiphytic bacteria isolated from species of Ulva have antibacterial activity against pathogenic Streptococcus pneumoniae and Klebsiella sp. especially that bacteria attached on Ulva compressa for the last one. Also the epiphytic bacteria attached on Ulva compressa and Dictyota spiralis have antibacterial activity against environmental and pathogenic bacteria. Depending on these results, we can say epiphytic bacteria attached on marine algae is expected to be potential resources of natural antibiotic products against bacteria in future.